Stress Experience of COVID-19 Patients as Reported by Psychological Supporters in South Korea: A Qualitative Study - Park, Hyein; Lee, Nabin; Lee, Jung Hyun; Lee, Dayoung; Kim, Kyoung Ae; Kim, Hyun-Seung; Oh, Eunhye; Ha, Ji Hyun; Hyun, So Yoen; Lee, Juyeon; Kim, Jiae; Jeon, Kyoungsun; et al. (Frontiers in Psychiatry, 2022)
Background: COVID-19 patients experience various stressors during the quarantine period and after release from quarantine. However, stressors experienced during each period remain unclear. Methods: A total of fifteen mental health experts from the integrated psychological support group for COVID-19 participated in this study. Psychological support was provided for the confirmed COVID-19 patients. Qualitative data were collected using Focus Group Interview (FGI). Results: During the quarantine period, difficulties of being diagnosed with COVID-19, concerns about recovery from COVID-19, stress related to quarantine, issues related to the treatment environment, and limited information about COVID-19 and communication were frequently reported. After release from quarantine, the reported main stressors include reinfection or reactivation, concerns about complications, and financial difficulties. Confusion as vectors and victims, stigma and discrimination, and conflicts within a family were observed during both periods. Conclusions: COVID-19 patients suffered various stressors during the quarantine period and after release from quarantine. Moreover, returning to their daily life required timely psychosocial support, intervention, and treatment for COVID-19 infection.